2004
DOI: 10.1097/01.psy.0000126201.12813.eb
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders in Obese Children and Adolescents

Abstract: These results highlight the importance of including a child psychiatric component in the treatment of obesity, which must engage the whole family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
66
5
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 26 publications
10
66
5
10
Order By: Relevance
“…Prevalence rates of psychiatric disorders in the present referred sample were lower than those in the studies by Britz et al [7] and Vila et al [46]. However, the former study also demonstrated substantially higher prevalence figures as compared with the latter.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Prevalence rates of psychiatric disorders in the present referred sample were lower than those in the studies by Britz et al [7] and Vila et al [46]. However, the former study also demonstrated substantially higher prevalence figures as compared with the latter.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the former study also demonstrated substantially higher prevalence figures as compared with the latter. This might partly be due to the differences in age group and to the assessment of lifetime diagnoses by Britz et al [7] but not by Vila et al [46]. Moreover, it is also important to distinguish between so called investigator-based interviews (K-SADS-R, KID-SCID, ChEDE) on the one hand and respondent-based interviews (M-CIDI) on the other hand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations